Application of crimped fibers in fracturing process

By combining the modified curled fibers with calcium hydroxide pellets, the problems of poor fiber dispersion and poor sand carrying effect in traditional fracturing technology are solved, and efficient sand carrying and sand protection are achieved in low-temperature reservoirs, reducing formation damage and cost.

CN119799310APending Publication Date: 2025-04-11CHINA OILFIELD SERVICES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510016222.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional fracturing technology faces problems such as proppant settlement, insufficient direction control of crack expansion, and proppant rebate. The existing fiber products have poor dispersion, large addition amount, poor effect, and the fibers cannot effectively carry sand in low-viscosity fracturing fluid.

Method used

The two-dimensional or three-dimensional crimped fibers obtained by modification treatment from polylactic acid fibers are used to mix them with calcium hydroxide pellets for fiber sand fracturing process in low-temperature reservoirs of 50°C to 90°C. The cross-sections of the modified fibers are X-type, Y-type and O-type, and the number of crimps is 6-12 pieces/25mm.

Benefits of technology

It improves the clamping force and friction between fibers, enhances the interaction between fibers and proppants, improves the sand carrying and sand prevention capabilities of fibers, reduces the amount of fibers, reduces damage to the formation, and achieves the sand carrying effect without adding synergists in the low-viscosity fracturing fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799310A_ABST
    Figure CN119799310A_ABST
Patent Text Reader

Abstract

The invention relates to application of crimped fibers in a fracturing process. When the two-dimensional crimped fibers are applied to a fracturing process, cohesive force and friction force between the fibers can be increased, so that the interaction between the fibers and between the fibers and a propping agent is improved, the dispersity of the fibers in fracturing fluid is improved, and the sand-carrying and sand-preventing capacities of the fibers are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil extraction, and in particular relates to application of a crimped fiber in a fracturing process. Background Art

[0002] In the process of oil and gas exploration and development, fracturing technology has been widely used and rapidly developed as an effective means of increasing production. Fracturing technology aims to generate cracks in formation rocks by injecting fluids at high pressure, thereby increasing the permeability and production capacity of oil and gas reservoirs. However, traditional fracturing technology faces many challenges, such as proppant sedimentation, insufficient control of crack extension direction, and proppant spitting. To solve these problems, fiber materials came into being. Through their unique physical and chemical properties, they significantly improved the effect and efficiency of fracturing operations. Fiber products can improve the sand carrying capacity of fracturing fluids, reduce excessive dependence on liquid viscosity, and reduce damage to reservoirs; at the same time, they can optimize proppant placement, solve the impact of poorly supported crack geometry on production capacity, and increase the effective crack support volume.

[0003] Current fiber products face problems such as poor dispersibility, large addition amount, and poor effect, which limit the application of fibers. In addition, the fiber sand-carrying products on the market will overflow from the proppant in low-viscosity fracturing fluids, and the sand-carrying effect cannot be achieved. Therefore, it is often necessary to add a synergist to achieve the adsorption of the fiber and the proppant to improve the sand-carrying effect; the synergist component is bentonite or a fiber-enhancing suspension material, which is generally harmful to the formation. Summary of the invention

[0004] In order to solve all or part of the above problems, the present invention aims to provide an application of a curled fiber in a fracturing process.

[0005] Specifically, the present invention provides the use of curled fibers in a fracturing process.

[0006] Furthermore, the curled fiber is a two-dimensional curled fiber or a three-dimensional curled fiber, wherein the curvature of the two-dimensional curled fiber in a two-dimensional plane is serrated.

[0007] Furthermore, the number of curls of the curled fiber per 25 mm is 6-12; and the cross section of the curled fiber is one of X-type, Y-type and O-type.

[0008] Furthermore, the fracturing process is a fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C; the curly fiber is a two-dimensional curly fiber or a three-dimensional curly fiber obtained by modifying polylactic acid fiber; the two-dimensional curly fiber or the three-dimensional curly fiber is mixed with calcium hydroxide granules and used in a fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C, wherein the molar ratio of the two-dimensional curly fiber or the three-dimensional curly fiber obtained after modification to the calcium hydroxide granules is 1:(1.5-3.5).

[0009] Furthermore, the auxiliary agent used to modify the polylactic acid fiber includes a plasticizer, and also includes one or more of a catalyst, an easily hydrolyzed polymer, and a degradation-promoting monomer; wherein the mass ratio of the plasticizer used in the modification process of the polylactic acid fiber to the polylactic acid fiber raw material is (0.2-2):100, the mass ratio of the catalyst used to the polylactic acid fiber raw material is (0-2):100, the mass ratio of the easily hydrolyzed polymer used to the polylactic acid fiber raw material is (3-12):100, and the mass ratio of the degradation-promoting monomer used to the polylactic acid fiber raw material is (2.5-11):100;

[0010] The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the polylactic acid fiber has a moisture content between 10% and 20%.

[0011] If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0012] Furthermore, the step of obtaining two-dimensional crimped fibers or three-dimensional crimped fibers by modifying the polylactic acid fibers comprises:

[0013] Prepare polylactic acid fiber, mix the prepared polylactic acid fiber and the additive, add the mixture into a twin-screw extruder, melt and disperse the materials in the twin-screw extruder, and finally extrude the materials through a die head, wherein the physical properties of the polylactic acid fiber are as follows: melting point 120° C.-130° C., 210° C. / 2.16 kg melt index 20.8;

[0014] The material extruded through the die is cooled and dried, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90Kpa and at 70°C for 24 hours to make the final moisture content of the material ≤100PPM;

[0015] Processing the material with a pelletizer to obtain material particles;

[0016] The granular material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; a lubricant with a concentration of 4% is added during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed inlet is set to 185°C, the temperature of the middle straight tube zone is set to 234°C, the temperature of the rear end of the straight tube zone is set to 230°C, and the spinning temperature is set to 230°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 68°C, and the second drawing temperature is 88°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%.

[0017] Furthermore, the fracturing process is a fiber-sand fracturing process for medium-temperature reservoirs at 90° C. to 150° C., and the curled fibers are two-dimensional curled fibers or three-dimensional curled fibers obtained by modifying polylactic acid fibers.

[0018] Furthermore, the auxiliary agent used to modify the polylactic acid fiber includes a dispersing plasticizer, and the dispersing plasticizer is triacetin; the mass ratio of the dispersing plasticizer to the polylactic acid fiber raw material is (0-2):100;

[0019] The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the polylactic acid fiber has a moisture content between 10% and 20%.

[0020] If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0021] Furthermore, the fracturing process is a fiber-sand fracturing process and a fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C, and the curly fiber is a two-dimensional curly fiber or a three-dimensional curly fiber obtained by modifying PET fiber; the two-dimensional curly fiber or the three-dimensional curly fiber is mixed with an oxidant and used in a fiber-sand fracturing process and a fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C;

[0022] The mass ratio of the oxidant to the two-dimensional curled fiber or the three-dimensional curled fiber obtained after modification is (0.5-3):100.

[0023] Furthermore, the auxiliary agent used to modify the PET fiber includes a plasticizer, and also includes calcium carbonate and / or a modified masterbatch; wherein the mass ratio of the plasticizer used in the process of modifying the PET fiber to the PET fiber raw material is (0.2-2):100, the mass ratio of the calcium carbonate used to the PET fiber raw material is (0-2):100, and the mass ratio of the modified masterbatch used to the PET fiber raw material is (2-4.3):100;

[0024] The oxidant is one or more of sodium hypochlorite, potassium iodide, sodium bromate, and ammonium persulfate;

[0025] The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the PET fiber has a moisture content between 10% and 20%;

[0026] If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0027] Furthermore, the step of obtaining two-dimensional crimped fibers or three-dimensional crimped fibers by modifying PET fibers comprises:

[0028] Prepare PET fiber, mix the prepared PET fiber and the additive, and then add the mixture into a twin-screw extruder, so that the material is melted and dispersed in the twin-screw extruder, and finally extruded through a die head, wherein the physical properties of the PET fiber are as follows: melting point 222-225° C., 230° C. / 2.16 kg melt index 22.8;

[0029] The material extruded through the die is cooled and dried, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90Kpa at 125°C for 6 hours to make the final moisture content of the material ≤200PPM;

[0030] Processing the material with a pelletizer to obtain material particles;

[0031] The granular material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; a lubricant with a concentration of 4% is added during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed inlet is set to 210°C, the temperature of the middle straight tube zone is set to 255°C, the temperature at the rear end of the straight tube zone is set to 250°C, and the spinning temperature is set to 255°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 72°C, and the second drawing temperature is 92°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%.

[0032] Furthermore, the length of the straightened curly fiber is 3-20 mm, the curly fiber is a uniform structure or a skin-core structure, and the fineness of the curly fiber is 1.2 denier-2 denier.

[0033] It can be seen from the above technical solution that the application of the crimped fiber provided by the present invention in the fracturing process has the following beneficial effects:

[0034] The curled fiber of the present invention is used in the fracturing process to increase the cohesion and friction between fibers, thereby improving the interaction between fibers and between fibers and proppants, improving the dispersion of fibers in fracturing fluid, and improving the sand carrying and sand prevention capabilities of fibers; and can achieve the purpose of reducing the amount of fiber under the same sand carrying effect, thereby reducing the cost of the fracturing process; and the curled fiber is applied to the fracturing process, and the fiber sand carrying effect can be achieved in the low-viscosity fracturing fluid without adding a synergist, thereby overcoming the problem of damaging the formation due to the addition of a synergist in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a comparison of the appearance of two-dimensional curly fibers and straight fibers. Figure 1 The left picture in the figure shows the appearance of a two-dimensional curled fiber. Figure 1 The right picture in the figure shows the appearance of straight fibers;

[0036] Figure 2 The mechanism of sand carrying and sand control of two-dimensional curled fibers;

[0037] Figure 3 This is a comparison of the dispersion of two-dimensional curly fibers and straight fibers within the same 30 seconds. Figure 3 The left picture in the figure shows the dispersion of two-dimensional curled fibers. Figure 3 The right picture in the figure shows the dispersion of straight fibers. DETAILED DESCRIPTION

[0038] In order to better understand the purpose, structure and function of the present invention, the application of a crimped fiber of the present invention in a fracturing process is further described in detail below in conjunction with the accompanying drawings.

[0039] A curly fiber refers to a fiber that is curved in a two-dimensional plane or in a three-dimensional space, wherein a fiber that is curved in a two-dimensional plane is a two-dimensional curly fiber, and a fiber that is curved in a three-dimensional space is a three-dimensional curly fiber. The embodiment of the present invention provides a new use of the curly fiber, that is, applying the curly fiber to a fracturing process.

[0040] Among them, for two-dimensional curled fibers, Figure 1 This is a comparison of the appearance of two-dimensional curly fibers and straight fibers. Figure 1 The left picture in the figure shows the appearance of a two-dimensional curled fiber. Figure 1 The right picture shows the appearance of straight fibers. Figure 1 It can be seen that the difference between the two-dimensional curled fiber and the straight fiber is that the two-dimensional curled fiber has curling. In the embodiment of the present invention, the curvature of the two-dimensional curled fiber in the two-dimensional plane is zigzag.

[0041] The invention aims to apply two-dimensional curled fibers or three-dimensional curled fibers to the fracturing process. Figure 2 The mechanism of sand carrying and sand control of two-dimensional curled fibers. Figure 2 The circles in the figure can be understood as proppant particles. Figure 2 It can be seen that the application of two-dimensional curled fibers in the fracturing process can increase the cohesion and friction between fibers, thereby improving the interaction between fibers and fibers, and between fibers and proppants, improving the dispersion of fibers in the fracturing fluid, and improving the sand carrying and sand prevention capabilities of fibers.

[0042] After the curled fiber is applied to the fracturing process in this embodiment, the fiber sand carrying effect and sand prevention effect can be achieved in the low-viscosity fracturing fluid without adding a synergist. That is, the curled fiber is applied to the fracturing process in this embodiment, and there will be no situation where the formation is damaged due to the need to add a proppant.

[0043] Secondly, the fiber is relatively expensive. Processing the fiber into curled fiber can achieve the advantage of significantly reducing the fiber usage while maintaining the same sand-carrying effect, thereby significantly reducing the cost of the fracturing process.

[0044] again, Figure 3 This is a comparison of the dispersion of two-dimensional curly fibers and straight fibers within the same 30 seconds. Figure 3 The left picture in the figure shows the dispersion of two-dimensional curled fibers. Figure 3 The right picture shows the dispersion of straight fibers. Figure 3 It can be seen that the two-dimensional curly fiber has better dispersibility than the straight fiber, and is more evenly dispersed in water and fracturing fluid in the same time.

[0045] Finally, the use of two-dimensional curled fibers in fracturing technology has the following advantages: because the curling of two-dimensional curled fibers is only formed in a two-dimensional plane, while the curling of three-dimensional curved fibers needs to be formed in three-dimensional space, the production process of two-dimensional curled fibers is relatively simple and the production cost is relatively low; because the curling of two-dimensional curled fibers is only formed in a two-dimensional plane, the morphology and performance of two-dimensional curled fibers are easier to control during processing than three-dimensional curled fibers; three-dimensional curled fibers are easy to clog pipelines and suction pumps, and it is difficult to add three-dimensional curled fibers during construction, while two-dimensional curled fibers have both dispersibility and sand carrying properties, and are easier to add.

[0046] Wherein, the number of curls of the curled fiber per 25 mm is 6-12.

[0047] Wherein, the cross section of the curled fiber is one of X-type, Y-type and O-type.

[0048] The length of the curled fiber after straightening is 3-20 mm.

[0049] The curled fiber is a uniform structure or a skin-core structure, wherein the skin-core structure refers to a structure in which there are structural differences in the fiber morphology along the radial direction.

[0050] The fineness of the crimped fiber is 1.2 denier to 2 denier. At the standard moisture regain, denier is defined as the weight (grams) of a fiber with a length of 9,000 meters. Specifically, denier refers to the mass in grams of a fiber with a length of 9,000 meters at the standard moisture regain. For example, if the weight of a fiber with a length of 9,000 meters is 2 grams, the fineness of the fiber is 2 denier, also expressed as 2D.

[0051] The crimped fiber material is at least one of degradable fiber, soluble fiber and non-degradable fiber. The degradable fiber is at least one of polylactic acid, polyglycolic acid, PCL and polyhydroxyalkanoate; the soluble fiber material is polyvinyl alcohol; the non-degradable fiber is at least one of PET, nylon, polyethylene, polypropylene and polyvinyl chloride.

[0052] Embodiment 1:

[0053] The fracturing process is a fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C; the curly fiber is a two-dimensional curly fiber or a three-dimensional curly fiber obtained by modifying polylactic acid fiber; the two-dimensional curly fiber or the three-dimensional curly fiber is mixed with calcium hydroxide granules and used in the fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C.

[0054] The raw materials of PLA fiber mainly come from starch-containing agricultural products such as corn, wheat or beets. These raw materials are renewable and can be obtained through planting, so PLA fiber has better sustainability; PLA fiber can be completely degraded into carbon dioxide and water by microorganisms in nature, which is an environmentally friendly degradation method that helps reduce plastic pollution; PLA fiber has significant advantages over PVA fiber in raw materials and sustainability, biodegradability, physical properties, application areas and comfort and other aspects; PVA dissolves and increases viscosity, while PLA fiber degrades without increasing viscosity and is renewable.

[0055] The polylactic acid fiber of this embodiment is conventional polylactic acid fiber, which shows slow degradation at 50°C-90°C. The hydrolysis reaction of polylactic acid has low reaction kinetics at this temperature, so it is necessary to perform modification processing on the basis of the raw material so that it can be applied to low-temperature reservoirs at 50°C to 90°C.

[0056] The idea of ​​modifying conventional polylactic acid fibers is to enhance the degradation effect through additives. The additives mainly include: plasticizers for reducing intermolecular interactions, catalysts that facilitate hydrolysis reactions, inorganic powders that promote degradation (calcium carbonate, calcium hydroxide), easily hydrolyzed polymers that help promote overall fiber degradation, and pro-degradation monomers that provide an acidic environment to promote the degradation of polylactic acid fibers. The purpose of the modification is to improve its degradation performance at 50℃-90℃, so that it can be degraded at low temperatures, thereby facilitating its application in low-temperature reservoirs at 50℃-90℃.

[0057] The auxiliary agent used to modify the polylactic acid fiber includes a plasticizer, and also includes one or more of a catalyst, an easily hydrolyzed polymer, and a degradation-promoting monomer. The mass ratio of the plasticizer used in the modification process of the polylactic acid fiber to the polylactic acid fiber raw material is (0.2-2):100, the mass ratio of the catalyst used to the polylactic acid fiber raw material is (0-2):100, the mass ratio of the easily hydrolyzed polymer used to the polylactic acid fiber raw material is (3-12):100, and the mass ratio of the degradation-promoting monomer used to the polylactic acid fiber raw material is (2.5-11):100.

[0058] Among them, the main function of the plasticizer is to weaken the secondary bonds between polymer molecules, namely the van der Waals force, thereby increasing the mobility of the polymer molecular chain. In specific implementation, for example, tributyl citrate (TBC for short) is used as a plasticizer, and the mass ratio of the plasticizer to the polylactic acid fiber raw material is, for example, 0.5:100.

[0059] The catalyst used is an ester exchange catalyst, which can attack the ester bond inside the molecule, reduce the reaction barrier, and enhance the activity of the ester bond, thereby facilitating the hydrolysis reaction. In specific implementation, for example, an ester exchange catalyst provided by Lanyue Technology is used. When the mass ratio of the catalyst to the polylactic acid fiber raw material is 1:100, the hydrolysis reaction rate is faster. When the amount of the catalyst is increased, the rate of the hydrolysis reaction increases slowly.

[0060] The easily hydrolyzed polymer in this embodiment is polycaprolactone (PCL), which is an easily hydrolyzed polymer with a low melting point and a degradation rate higher than that of polylactic acid fiber (PLA). The blending of the two helps to promote the degradation of the entire fiber, and the defects generated by the preferential degradation can promote the faster degradation of PLA. Among them, when the mass ratio of the easily hydrolyzed polymer to the polylactic acid fiber raw material is 5:100, the degradation of the entire fiber is significantly promoted.

[0061] The degradation-promoting monomer of this embodiment is used to preferentially degrade inside the fiber, provide an acidic environment, and then promote the degradation of the polylactic acid fiber. The degradation-promoting monomer of this embodiment is PLA polyol, which is a small molecule lactic acid oligomer. In specific implementation, for example, the mass ratio of the degradation-promoting monomer to the polylactic acid fiber raw material is 5:100.

[0062] Regarding the above-mentioned auxiliary agent, after using it to modify the polylactic acid fiber, after spinning and testing, it was found that the heat resistance of the curly fiber obtained after modification with 0.5% plasticizer met the standard, that is, it met the corresponding use requirements within the range of 50°C to 90°C.

[0063] The molar ratio of the two-dimensional curled fibers or three-dimensional curled fibers obtained after modification to the calcium hydroxide granules is 1:(1.5-3.5).

[0064] The two-dimensional curled fiber or three-dimensional curled fiber modified in this embodiment is mixed with calcium hydroxide pellets and used in the fiber sand fracturing process of low-temperature reservoirs at 50°C to 90°C, which can meet the degradation requirements, that is, it is slightly degraded during the fracturing stage (within 2 hours). After the fracturing stage, the lactic acid and calcium hydroxide obtained by hydrolysis of polylactic acid are rapidly degraded by acid-base neutralization, and the degradation rate reaches more than 98% after 30 days. Among them, the calcium hydroxide pellets here refer to 20-40 mesh calcium hydroxide pellets. When the molar ratio of the two-dimensional curled fiber or three-dimensional curled fiber obtained after modification to the calcium hydroxide pellets is 1:2, the degradation rate reaches more than 96.7% after 30 days.

[0065] The step of obtaining two-dimensional crimped fibers or three-dimensional crimped fibers by modifying polylactic acid fibers comprises:

[0066] Step S11: preparing polylactic acid fiber, mixing the prepared polylactic acid fiber and an additive, and adding the mixed material into a twin-screw extruder, so that the material is melted and dispersed in the twin-screw extruder, and finally extruded through a die head, wherein the physical properties of the polylactic acid fiber are: melting point 120°C-130°C, 210°C / 2.16kg melt index 20.8;

[0067] Step S12: cooling and drying the material extruded through the die head, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90 KPa at 70° C. for 12 hours, so that the final moisture content of the material is ≤100 PPM;

[0068] Step S13: using a pelletizer to process the material to obtain material particles;

[0069] Step S14: The granular material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; wherein a lubricant with a concentration of 4% is added during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed port is set to 185°C, the temperature of the middle straight tube zone is set to 234°C, the temperature of the rear end of the straight tube zone is set to 230°C, and the spinning temperature is set to 230°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 68°C, and the second drawing temperature is 88°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0, wherein the total drawing ratio is equal to the first drawing ratio multiplied by the second drawing ratio, for example, the first drawing ratio is 3.35, and the second drawing ratio is 1.2; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%.

[0070] Among them, the lubricant added during the spinning process can provide the balanced lubricity, cohesion and electrostatic protection required for uniform processing. It also has excellent wetting properties and can be used as a spinning finishing agent.

[0071] Again, the two-dimensional curled fiber used in low-temperature storage uses low-light pure polylactic acid fiber as the main material. The physical properties and various processes of low-light pure polylactic acid fiber are described as follows:

[0072] Its physical properties are: melting point 120℃-130℃, 210℃ / 2.16kg melt index 20.8;

[0073] Drying temperature: Low-light pure polylactic acid has a low melting point, so the drying temperature is reduced to 70°C. Taking temperature factors into consideration, the drying time is set to 24h;

[0074] Spinning temperature: The feed port is set at 185°C. Compared with the medium-temperature fiber, the temperature is lowered to prevent the feed port from being blocked after the melting point is lowered. The middle temperature is lowered to 234°C, and the tail temperature is slightly lowered to 230°C to prevent high-temperature degradation of the material as much as possible. Considering the melting point and melt index comprehensively, the spinning temperature is set at 230°C.

[0075] The spinning frequency affects the fiber thickness. The spinning frequency is determined by comprehensive calculation based on melt density, metering pump parameters, and draft ratio. After the fiber size and draft ratio are determined, the frequency parameters of the same material remain basically unchanged. The melt density of polylactic acid fiber is 1.13g / cm 3 , as long as the products are of the same specifications, the spinning frequency remains unchanged;

[0076] Drawing temperature: The glass transition temperature of polylactic acid is 60°C. The drawing temperature needs to be higher than 60°C. The first drawing is responsible for drawing, and the second drawing is responsible for drawing and shaping, so the second drawing temperature is high.

[0077] Drafting ratio: According to production experience, the drafting ratio is set at 3.6-4.8. Low drafting ratio will lead to low strength, and high drafting ratio will lead to poor toughness. It is generally set at around 4.0 times.

[0078] Finally, the two-dimensional crimped fiber or three-dimensional crimped fiber obtained in the above-mentioned embodiment 1 is a wet fiber with a moisture content of 10% to 20%, which saves energy consumption and reduces production costs. In addition, the wet fiber has better dispersibility and is easier to add when used in on-site construction. In order to solve the problem of freezing of wet fiber in winter construction, if the crimped fiber is used in winter construction, antifreeze needs to be added, and the antifreeze is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0079] Embodiment 2:

[0080] The fracturing process is a fiber-sand fracturing process for medium-temperature reservoirs at 90° C. to 150° C., and the curled fibers are two-dimensional curled fibers or three-dimensional curled fibers obtained by modifying polylactic acid fibers.

[0081] For application in medium-temperature reservoirs, medium-temperature polylactic acid fiber materials are used, such as high-gloss pure polylactic acid. The physical properties of high-gloss pure polylactic acid fiber are: melting point 165℃-180℃, 210℃ / 2.16kg melt index 20.

[0082] In the specific implementation, the medium-temperature polylactic acid fiber is modified to obtain a two-dimensional curled fiber or a three-dimensional curled fiber that can be applied to the medium-temperature reservoir. The auxiliary agent used includes a dispersing plasticizer, and the dispersing plasticizer is triacetin; the mass ratio of the dispersing plasticizer to the polylactic acid fiber raw material is (0-2):100.

[0083] Triacetin is a dispersing plasticizer and hydrolysis promoter. Its main function is to enhance the mobility of material molecules after being added to the material, promote the entry of water molecules into the material, and accelerate the degradation of the fiber.

[0084] After modification of the medium-temperature polylactic acid fiber material, it was found that: when the mass ratio of triacetin to polylactic acid fiber raw materials is 1:100, the modified curly fiber can meet the high temperature 150°C heat resistance requirement, does not degrade during the fracturing stage, and degrades 98% in 30 days at a low temperature of 90°C, which can meet the use requirements of medium-temperature materials.

[0085] Finally, the two-dimensional crimped fiber or three-dimensional crimped fiber obtained in the above-mentioned embodiment 2 is a wet fiber with a moisture content between 10% and 20%, which saves energy consumption, reduces production costs, and has better dispersibility and is easier to add when used for on-site construction. In order to solve the problem of freezing of wet fibers in winter construction, if the crimped fibers are used in winter construction, antifreeze needs to be added, and the antifreeze is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0086] Embodiment three:

[0087] The fracturing process is a fiber-sand fracturing process and a fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C. The curled fiber is a two-dimensional curled fiber or a three-dimensional curled fiber obtained by modifying PET fiber. The two-dimensional curled fiber or the three-dimensional curled fiber is mixed with an oxidant and used in the fiber-sand fracturing process and the fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C.

[0088] Regarding the two-dimensional curled fibers or three-dimensional curled fibers obtained by modifying PET fibers, PET fibers have significant advantages over PVA fibers in terms of physical and mechanical properties, chemical stability, thermal properties, wide application and other aspects.

[0089] The mass ratio of the oxidant to the two-dimensional curled fiber or the three-dimensional curled fiber obtained after modification is (0.5-3):100.

[0090] In specific implementation, when the mass ratio of the oxidant to the PET curly fiber is 1:100, the degradation rate of the PET curly fiber is 98% after 30 days; when the mass ratio of the oxidant to the PET curly fiber is 0.5:100, the degradation rate of the PET curly fiber is 95% after 30 days; and when the mass ratio of the oxidant to the PET curly fiber is greater than 1.5:100, the degradation rate of the PET curly fiber increases slowly, but the increase is not as large as the degradation increase in the range of (0.5-1.5):100.

[0091] The auxiliary agent used to modify the PET fiber includes a plasticizer, calcium carbonate and / or a modified masterbatch. The mass ratio of the plasticizer used in the modification process of the PET fiber to the PET fiber raw material is (0.2-2):100, the mass ratio of the calcium carbonate used to the PET fiber raw material is (0-2):100, and the mass ratio of the modified masterbatch used to the PET fiber raw material is (2-4.3):100.

[0092] Specifically, during the modification of PET fibers, the main function of the plasticizer is to enhance the mobility of the material molecules, promote the entry of water molecules into the material, and accelerate the degradation of the fibers. In specific implementation, the mass ratio of the plasticizer to the PET fiber raw material is, for example, 0.5:100, at which the fiber degrades faster.

[0093] During the modification process of PET fiber, modified masterbatch is also added. The modified masterbatch is a reaction-promoting degradation agent, which is made by injecting degradation organic additives into traditional polymer materials. The active chemical activity caused by the additive introduces the polymer material into the biodegradation stage, leaving only natural gas and bioenergy in the end, that is, the modified masterbatch can destroy the covalent bond of the molecular chain at high temperature. In specific implementation, the mass ratio of the modified masterbatch to the PET fiber raw material is, for example, 3:100.

[0094] The two-dimensional curled fiber or three-dimensional curled fiber modified in this embodiment is mixed with an oxidant and used in the fiber sand fracturing process and fiber sand control fracturing process of 150℃-200℃ high-temperature reservoir, which can meet the degradation requirements, that is, micro-degradation in the fiber sand fracturing and fiber sand control fracturing stages. Micro-degradation means that the degradation rate is less than 0.02%, and it degrades rapidly after the fracturing stage, and the degradation rate is greater than or equal to 95%. The oxidant plays an oxidizing role in the degradation process. In specific implementation, for example, one or more of sodium hypochlorite, potassium iodide, sodium bromate, and ammonium persulfate are used as oxidants.

[0095] The steps of obtaining two-dimensional curled fibers or three-dimensional curled fibers by modifying PET fibers include:

[0096] Step S21: preparing PET fiber, mixing the prepared PET fiber and the additive and adding the mixture into a twin-screw extruder, so that the materials are melted and dispersed in the twin-screw extruder, and finally extruded through a die head, wherein the physical properties of the PET fiber are as follows: melting point 222-225° C., 230° C. / 2.16 kg melt index 22.8;

[0097] Step S22: cooling and drying the material extruded through the die head, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90 KPa at 125° C. for 6 hours, so that the final moisture content of the material is ≤200 PPM;

[0098] Step S23: using a pelletizer to process the material to obtain material particles;

[0099] Step S24: The particulate material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; a lubricant is added at a concentration of 4% during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed port is set to 210°C, the temperature of the middle straight tube zone is set to 255°C, the temperature of the rear end of the straight tube zone is set to 250°C, and the spinning temperature is set to 255°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 72°C, and the second drawing temperature is 92°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0, for example, the first drawing ratio is 3.35, and the second drawing ratio is 1.2; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%. Among them, lubricating oils can provide balanced lubricity, cohesion and static protection required for uniform processing, and also have excellent wetting properties and can be used as spinning finishing agents.

[0100] Again, the physical properties of easily hydrolyzed PET fiber and the description of each process are as follows:

[0101] Physical properties: melting point 222-225℃, melt index 22.8 at 230℃ / 2.16kg.

[0102] Drying temperature: PET has a high melting point and a crystallization temperature of about 125°C, so the drying temperature is set to 125°C. Considering the temperature factor, the drying time is set to 6h.

[0103] Spinning temperature: The feed inlet is set at 210℃. Compared with the medium-temperature fiber material, the temperature is increased to prevent the material from being softened after the melting point is increased and conveyed; the middle temperature is increased to 255℃; the tail temperature is slightly reduced by 250℃ to prevent high temperature degradation of the material as much as possible. Considering the melting point and melt index comprehensively, the spinning temperature is set at 255℃.

[0104] The spinning frequency affects the thickness of the fiber. The melt density of PET is higher than that of polylactic acid, so under the same draft ratio process, the spinning frequency drops to 15.29Hz.

[0105] Stretching temperature: The glass transition temperature of PET is 70℃; the stretching temperature needs to be higher than 20℃. The first stretching is responsible for stretching, and the second stretching is responsible for stretching and shaping, so the second stretching temperature is set at 92℃.

[0106] Drafting ratio: According to production experience, the drafting ratio is set at 3.6-4.8. Low drafting ratio will lead to low strength, and high drafting ratio will lead to poor toughness; it is generally set at around 4.0 times.

[0107] Again, the two-dimensional crimped fiber or three-dimensional crimped fiber obtained in the above-mentioned Example 3 is a wet fiber with a moisture content of 10% to 20%, which saves energy consumption and reduces production costs. In addition, the wet fiber has better dispersibility and is easier to add when used for on-site construction. In order to solve the problem of freezing of wet fiber in winter construction, if the crimped fiber is used in winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

[0108] In summary, the curled fibers of the embodiments of the present invention can be used in the fracturing process of reservoirs in various temperature ranges, and corresponding fibers are prepared in each temperature range to obtain curled fibers with relatively ideal sand carrying and sand prevention effects, thereby providing theoretical and technical support for the construction of fracturing processes for reservoirs in various temperature ranges.

[0109] The application of two-dimensional curled fibers in the fracturing process is described below by means of specific examples.

[0110] Embodiment 4

[0111] Application of two-dimensional curled fiber in fiber-sand fracturing process, wherein the material of the two-dimensional curled fiber is degradable fiber, soluble fiber or non-degradable fiber, and two-dimensional curled fiber of different materials is selected according to different well conditions. Example 1 Well conditions are:

[0112] Example 1 well is a coalbed methane well. The well is drilled to a vertical depth of 1597.44m, an oblique depth of 1641m, a strike of about 85°-92°, a large formation dip of about 47°-49°, and a formation dip of about 175°-182°. According to the rock cuttings photos of the coal in Example 1 well, the coal rock characteristics of the two coal seams are black, highly carbonized, dirty, brittle, well-developed cleavage, and glassy luster. It is judged that the coal body structure of the coal seam is mainly a fragmented structure. The gas content of the well is 6.2m 3 / t-7.3m 3 / t. The average well temperature of the upper and lower coal seam sections of Example 1 well is 31.25℃ and 32.34℃ respectively. According to the drainage data of the producing wells around Example 1 well, the coal seam pressure of the well is predicted to be 11.8MPa~13.8MPa.

[0113] According to the well conditions and the results of the indoor evaluation, the serrated, X-shaped cross section, 8 curls / 25mm, 6mm in length, 1.2D fineness, uniform structure, and two-dimensional curled fibers modified with degradable polylactic acid are selected for use in fiber-sand fracturing. After screening, the curled fibers are added at a mass concentration of 0.1% to 0.5% of the volume of the fracturing fluid, preferably at a mass concentration of 0.2% of the volume of the fracturing fluid. The specific pumping procedure is shown in Table 1, where the slippery water + fiber in the remarks column of Table 1 represents low-viscosity slippery water + two-dimensional curled fiber.

[0114] Table 1: Example 1 Well Pumping Program

[0115]

[0116]

[0117] Embodiment 5

[0118] Application of two-dimensional curled fiber in fiber sand control fracturing technology:

[0119] The material of the two-dimensional crimped fiber is non-degradable fiber or degradable fiber that degrades slowly at reservoir temperature. Different two-dimensional crimped fibers are selected according to different well conditions. The well conditions of Example 2 are:

[0120] Well 2 is a tight sandstone gas well, with an artificial well bottom position of 2355.87m, and the reformed interval is 2247.5-2267.2m (measured depth) and 1989.7-2007.7m (vertical depth). The well has developed 8.0m (vertical thickness) / 3 layers of Class I gas layers and 6.2m (vertical thickness) / 4 layers of Class II gas layers. The effective reservoir physical properties range: porosity 7.3%~9.7%, 9.0% on average (thickness weighted); permeability 0.27~0.87mD, 0.64mD on average (thickness weighted). The lithology and physical properties of the well are mainly gray medium-coarse-grained lithic sandstone and feldspar lithic sandstone. The median grain size of the sandstone is 0.39mm on average, mainly distributed in the range of 0.25~1.00mm, mainly medium-coarse-grained sandstone. The structural characteristics near the well are stable, and there are no large-scale faults around it. The average well temperature of the reservoir in Example 2 is 53.8℃.

[0121] According to the well conditions and the results of the indoor evaluation, the material of the serrated, X-shaped cross section, 8 crimps / 25mm, 6mm in length, 1.5D in fineness, uniform structure, and two-dimensional crimped fiber is selected as non-degradable PET. After screening, the two-dimensional crimped fiber is added at a mass concentration of 1% to 10% of the proppant volume, preferably at a concentration of 5%. The specific pumping procedure is shown in Table 2.

[0122] Table 2: Example 2 Well Pumping Program

[0123]

[0124]

[0125] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.

[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. Application of curly fiber in fracturing process.

2. The use according to claim 1, characterized in that: The curled fiber is a two-dimensional curled fiber or a three-dimensional curled fiber, wherein the bending of the two-dimensional curled fiber in a two-dimensional plane is zigzag-shaped.

3. The use according to claim 1, characterized in that: The number of curls of the curled fiber per 25 mm is 6-12; the cross section of the curled fiber is one of X-type, Y-type and O-type.

4. The use according to claim 1, characterized in that: The fracturing process is a fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C; the curly fiber is a two-dimensional curly fiber or a three-dimensional curly fiber obtained by modifying polylactic acid fiber; the two-dimensional curly fiber or the three-dimensional curly fiber is mixed with calcium hydroxide granules and used in the fiber-and-sand fracturing process for low-temperature reservoirs of 50°C to 90°C, wherein the molar ratio of the two-dimensional curly fiber or the three-dimensional curly fiber obtained after modification to the calcium hydroxide granules is 1:(1.5-3.5).

5. The use according to claim 4, characterized in that: The auxiliary agent used to modify the polylactic acid fiber includes a plasticizer, and also includes one or more of a catalyst, an easily hydrolyzed polymer and a degradation-promoting monomer; wherein the mass ratio of the plasticizer used in the process of modifying the polylactic acid fiber to the polylactic acid fiber raw material is (0.2-2):100, the mass ratio of the catalyst used to the polylactic acid fiber raw material is (0-2):100, the mass ratio of the easily hydrolyzed polymer used to the polylactic acid fiber raw material is (3-12):100, and the mass ratio of the degradation-promoting monomer used to the polylactic acid fiber raw material is (2.5-11):100; The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the polylactic acid fiber has a moisture content between 10% and 20%. If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

6. The use according to claim 4, characterized in that: The steps of obtaining two-dimensional crimped fibers or three-dimensional crimped fibers by modifying polylactic acid fibers include: Prepare polylactic acid fiber, mix the prepared polylactic acid fiber and the additive, add the mixture into a twin-screw extruder, melt and disperse the materials in the twin-screw extruder, and finally extrude the materials through a die head, wherein the physical properties of the polylactic acid fiber are as follows: melting point 120° C.-130° C., 210° C. / 2.16 kg melt index 20.8; The material extruded through the die is cooled and dried, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90Kpa and at 70°C for 24 hours to make the final moisture content of the material ≤100PPM; Processing the material with a pelletizer to obtain material particles; The granular material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; a lubricant with a concentration of 4% is added during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed inlet is set to 185°C, the temperature of the middle straight tube zone is set to 234°C, the temperature of the rear end of the straight tube zone is set to 230°C, and the spinning temperature is set to 230°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 68°C, and the second drawing temperature is 88°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%.

7. The use according to claim 1, characterized in that: The fracturing process is a fiber-sand fracturing process for medium-temperature reservoirs at 90° C. to 150° C., and the curled fibers are two-dimensional curled fibers or three-dimensional curled fibers obtained by modifying polylactic acid fibers.

8. The use according to claim 7, characterized in that: The auxiliary agent used to modify the polylactic acid fiber includes a dispersing plasticizer, and the dispersing plasticizer is triacetin; the mass ratio of the dispersing plasticizer to the polylactic acid fiber raw material is (0-2):100; The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the polylactic acid fiber has a moisture content between 10% and 20%. If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

9. The use according to claim 1, characterized in that: The fracturing process is a fiber-sand fracturing process and a fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C, and the curly fiber is a two-dimensional curly fiber or a three-dimensional curly fiber obtained by modifying PET fiber; the two-dimensional curly fiber or the three-dimensional curly fiber is mixed with an oxidant and used in the fiber-sand fracturing process and the fiber-sand-proof fracturing process for high-temperature reservoirs at 150°C-200°C; The mass ratio of the oxidant to the two-dimensional curled fiber or the three-dimensional curled fiber obtained after modification is (0.5-3):

100.

10. The use according to claim 9, characterized in that: The auxiliary agent used to modify the PET fiber includes a plasticizer, and also includes calcium carbonate and / or a modified masterbatch; wherein the mass ratio of the plasticizer used in the process of modifying the PET fiber to the PET fiber raw material is (0.2-2):100, the mass ratio of the calcium carbonate used to the PET fiber raw material is (0-2):100, and the mass ratio of the modified masterbatch used to the PET fiber raw material is (2-4.3):100; The oxidant is one or more of sodium hypochlorite, potassium iodide, sodium bromate, and ammonium persulfate; The two-dimensional crimped fiber or three-dimensional crimped fiber obtained by modifying the PET fiber has a moisture content between 10% and 20%; If the curly fiber is used for winter construction, an antifreeze agent needs to be added, and the antifreeze agent is at least one of ethylene glycol, propylene glycol, glycerol, methanol, and ethanol.

11. The use according to claim 10, characterized in that: The steps of obtaining two-dimensional crimped fibers or three-dimensional crimped fibers by modifying PET fibers include: Prepare PET fiber, mix the prepared PET fiber and the additive, and then add the mixture into a twin-screw extruder, so that the material is melted and dispersed in the twin-screw extruder, and finally extruded through a die head, wherein the physical properties of the PET fiber are as follows: melting point 222-225° C., 230° C. / 2.16 kg melt index 22.8; The material extruded through the die is cooled and dried, wherein the drying process is carried out in a vacuum environment with a vacuum degree greater than or equal to 90Kpa at 125°C for 6 hours to make the final moisture content of the material ≤200PPM; Processing the material with a pelletizer to obtain material particles; The granular material is spun by a spinning machine to obtain two-dimensional curly fibers or three-dimensional curly fibers; a lubricant with a concentration of 4% is added during the spinning process; the spinning temperature is controlled as follows: the temperature at the feed inlet is set to 210°C, the temperature of the middle straight tube zone is set to 255°C, the temperature at the rear end of the straight tube zone is set to 250°C, and the spinning temperature is set to 255°C; the drawing temperature is controlled as follows: the water temperature of the oil bath is 45°C, the first drawing temperature is 72°C, and the second drawing temperature is 92°C; the drawing ratio is controlled as follows: the oil bath drawing ratio is 1.05, and the total drawing ratio is 4.0; the obtained two-dimensional curly fibers or three-dimensional curly fibers are wet fibers with a moisture content between 10% and 20%.

12. The use according to claim 1, characterized in that: The length of the straightened curled fiber is 3-20 mm, the curled fiber is a uniform structure or a skin-core structure, and the fineness of the curled fiber is 1.2 denier-2 denier.